2001
DOI: 10.1016/s0921-5093(00)01851-7
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the wettability characteristics of polymethyl methacrylate (PMMA) by means of CO2, Nd:YAG, excimer and high power diode laser radiation

Abstract: The surface of the bio-material polymethyl methacrylate (PMMA) was treated with CO 2 , Nd:YAG, excimer and high power diode laser (HPDL) radiation. The laser radiation was found to effect varying degrees of change to the wettability characteristics of the material depending upon the laser used. It was observed that interaction with CO 2 , Nd:YAG and HPDL effected very little change to wettability characteristics of the PMMA. In contrast, interaction of the PMMA with excimer laser radiation resulted an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 43 publications
7
44
2
1
Order By: Relevance
“…This laser radiation can also modify the surface chemistry of polymers. In this case, the polar component of the surface energy can be considerably increased, and the wettability can be promoted (see e.g., [42]). …”
Section: Process Fundamentalsmentioning
confidence: 99%
“…This laser radiation can also modify the surface chemistry of polymers. In this case, the polar component of the surface energy can be considerably increased, and the wettability can be promoted (see e.g., [42]). …”
Section: Process Fundamentalsmentioning
confidence: 99%
“…It can be seen that the apparent γ P increases by up to 4.12 mJm -2 for the rougher sample (sample C9), whereas the γ D was reduced at most by 12.22 mJm -2 . As it is γ P of the surface energy that plays the major role in determining the contact angle it can be seen that these results also do not correspond with existing theory.For instance, Lawrence and Li [25] stated that a laser-induced increase in the γ P …”
mentioning
confidence: 99%
“…Indeed, work conducted by Zhang et al [56] found that signi®cant improvements in the bond strength of a Si 3 N 4 ceramic could be realized only when excimer laser treatment of a structural alloy steel (SAE 4340) resulted in surface melting. Similarly, Lawrence and Li [57] observed a sharp reduction in the contact angle at the point of melting onset of amalgamated oxide compound grout (AOCG) after HPDL treatment and a small but discernible increase in the contact angle with the generation of a rougher surface at higher power levels.…”
Section: E Ects Of Solidi®ed Microstructures and Surface Melting On Cmentioning
confidence: 86%